Primary Tumor Sidedness, RAS and BRAF Mutations and MSI Status as Prognostic Factors in Patients with Colorectal Liver Metastases Treated with Surgery and Thermal Ablation: Results from the Amsterdam Colorectal Liver Met Registry (AmCORE) - Madelon Dijkstra (Biomedicines, 2021)
The aim of this study was to assess primary tumor sidedness of colorectal cancer (CRC), rat sarcoma viral oncogene homolog (RAS) and v-raf murine sarcoma viral oncogene homolog B (BRAF) mutations and microsatellite instability (MSI) status as prognostic factors predicting complications, survival outcomes, and local tumor progression (LTP) following surgery and thermal ablation in patients with colorectal liver metastases (CRLM). This Amsterdam Colorectal Liver Met Registry (AmCORE) based study included 520 patients, 774 procedures, and 2101 tumors undergoing local treatment (resection and/or thermal ablation) from 2000 to 2021. Outcomes following local treatment were analyzed for primary tumor sidedness of CRC, RAS, and BRAF mutations and MSI status. The Kaplan–Meier method was used to estimate local tumor progression-free survival (LTPFS), local control (LC), distant progression-free survival (DPFS), and overall survival (OS). Uni- and multivariable analyses were performed based on Cox proportional hazards model. The chi-square test was used to analyze complications. Complications (p = 0.485), OS (p = 0.252), LTPFS (p = 0.939), and LC (p = 0.423) was not associated with tumor-sidedness. Compared to right-sided colon cancer (CC) (reference HR 1.000), DPFS was superior for left-sided CC and rectal cancer (p = 0.018) with an HR for left-sided CC of 0.742 (95% CI, 0.596–0.923) and for RC of 0.760 (95% CI, 0.597–0.966). Regarding RAS mutations, no significant difference was found in OS (p = 0.116). DPFS (p = 0.001), LTPFS (p = 0.039), and LC (p = 0.025) were significantly lower in the RAS mutation group. Though no difference in LTPFS was found between RAS wildtype and RAS mutated CRLM following resection (p = 0.532), LTPFS was worse for RAS mutated tumors compared to RAS wildtype following thermal ablation (p = 0.037). OS was significantly lower in the BRAF mutation group (p < 0.001) and in the MSI group (p < 0.001) following local treatment, while both did not affect DPFS, LTPFS, and LC. This AmCORE based study suggests the necessity of wider margins to reduce LTP rates in patients with RAS mutated CRLM, especially for thermal ablation. Upfront knowledge regarding molecular biomarkers may contribute to improved oncological outcomes.